Evidence for diffusing atomic oxygen uncovered by separating reactants with a semi-permeable nanocapsule barrier. Issue 12 (17th December 2018) - Omlid, Sara M.; Dergunov, Sergey A.; Isor, Ankita; Sulkowski, Kathryn L.; Petroff, John T.; Pinkhassik, Eugene; McCulla, Ryan D.
Abstract : Ground-state atomic oxygen [O( 3 P)] is an oxidant whose formation in solution was proposed but never proven. Abstract : Ground-state atomic oxygen [O( 3 P)] is an oxidant whose formation in solution was proposed but never proven. Polymer nanocapsules were used to physically separate dibenzothiophene S-oxide (DBTO), a source of O( 3 P), from an O( 3 P)-accepting molecule. Irradiation of polymer nanocapsules loaded with DBTO resulted in oxidation of the O( 3 P)-acceptor placed outside nanocapsules. The results rule out a direct oxygen atom transfer mechanism and are consistent with freely diffusing O( 3 P) as the oxidant.